Perhitungan Sumberdaya Batu Granit Pada Quarry PT Mandiri Karya Makmur Dengan Metode Cross Section dan Metode Cut And Fill: Calculation of Granit Stone Resource In Quarry PT Mandiri Karya Makmur With Cross Section And Cut And Fill Method - Zuhirmanto, Zuhirmanto; Mardiah, Mardiah; Irvani, Irvani (MINERAL, 2018)
Resource calculation studies are an important task in evaluating a mining project. Reserve calculation using the method of cross section and method cut and fill in mining area with extensive Active Block 8 hectares, with elevation limit of mining activity 60 m above sea level. The results of the resource volume of granite using method cross section within the cross section 15, 20 and 25 m is 1.436.967,28 m3, 1.435.887,56 m3 and 1.435.162,056 m3 tonnase 3.736.114,927 tons 3.733.307,656 tons and 3.731.421,345 tons, granite stone resource volume using cut and fill method is 1.437.398,157 m3 with 3.737.235,209 tons tonnage. The results of calculations using the method of cross section with a distance of 15 m smaller cross section 430,877 m3 or 0,03% of the cut and fill method, method of cross section with a distance of 20 m smaller cross section 1.510,597 m3, or 0,11% of the cut and fill method , cross section method with cross-sectional distance 25 m smaller 2.236,101 m3 or 0,16% from method cut and fill. The result of the calculation of the life of mine of PT Mandiri Karya Makmur is based on the calculation of the amount of resources used method cut and fill with a mine life of 31,14 years, cross section method sectional distance of 15 m with a mine life of 31,13 years, cross section method sectional distance of 20 m with a mine life 31,11 years and cross section method of cross- sectional distance of 25 m with mine life of 31,09 years.